2019
DOI: 10.1111/scd.12418
|View full text |Cite
|
Sign up to set email alerts
|

Patients with head and neck cancers' oral health knowledge, oral health‐related quality of life, oral health status, and adherence to advice on discharge to primary dental care: A prospective observational study

Abstract: Aims This prospective observational study set out to assess patients' oral health knowledge, oral health related quality of life (OHRQoL) and status immediately posttherapy, and adherence with oral health behaviors posttreatment with radiotherapy for head and neck cancer (HaNC). Methods A prospective observational study post HaNC therapy. At time one (T1), prior to discharge to primary dental care, oral health knowledge, OHRQoL, and status were assessed and dental health advice was delivered. At time two (T2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The QoL measurement was performed at different times, since the initial consultation; throughout DT, including periodontics, extraction, endodontics, and dentistry; at the end of DT; and in the follow-up of 1 year and 2 months post-DT. Barrios, Tsakos, García-Medina, Martínez-Lara and Bravo (2014) reported that the majority of head and neck cancer patients had five or more impacts on QoL and 97% with at least one impact, just like Abed et al (2019), with an average of eight per patient, including pain, social and functional impairment. Other studies (Barrios et al, 2015;Becker et al, 2012;Viet, Corby, Akinwande & Schmidt, 2014) also reported a negative physical impact on the health-related QoL of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The QoL measurement was performed at different times, since the initial consultation; throughout DT, including periodontics, extraction, endodontics, and dentistry; at the end of DT; and in the follow-up of 1 year and 2 months post-DT. Barrios, Tsakos, García-Medina, Martínez-Lara and Bravo (2014) reported that the majority of head and neck cancer patients had five or more impacts on QoL and 97% with at least one impact, just like Abed et al (2019), with an average of eight per patient, including pain, social and functional impairment. Other studies (Barrios et al, 2015;Becker et al, 2012;Viet, Corby, Akinwande & Schmidt, 2014) also reported a negative physical impact on the health-related QoL of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…For QoL research, there is no gold standard questionnaire, with a variety (Karimi et al, 2019) including OHIP-14 (Abed et al, 2019;Stuani et al, 2018), OHIP-49 (Fromm et al, 2019;Gotfredsen & Abdullah, 2015), questionnaires from the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 / QLQ-H / N35 (Karimi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations